Unpacking the innovation toolbox for design research and practice. (21st March 2019) - Montagna, Francesca; Cantamessa, Marco
Abstract : The terms design and innovation are intuitively related, but the relationship between these two concepts is more complex and subtle than it appears at first sight. Few authors have made rigorous attempts to explore this relationship in depth, and the contributions present in the literature generally suffer the specialist backgrounds on which they are grounded. Consequently, this paper provides a high-level synthesis of the innovation management domain and defines an original framework that allows the positioning of the concepts from Innovation Management that are most relevant for scholars and practitioners operating in the Design domain. Specifically, this framework provides a concise representation of the typologies of innovation activities along the technology lifecycle, and associates them to their business implications and to technical and organizational implications on the design process. This framework allows scholars and practitioners from both fields to identify the typical design challenges that are inherent to each type of innovation activity, and to evaluate the suitability of specific support methods and tools.